Implementasi Manajemen Strategi Dalam Meningkatkan Mutu Pendidikan - Dwi Setyaningsih (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2022)
This research is driven by the quality of education phenomenon, which continues to move and change, and its specifications and qualifications will continue to increase with the times. This study aims to determine the implementation of strategic management in improving the quality of education. This research was conducted at SD Islam de Green Camp Tanjungpinang. The approach taken is qualitative. The method used is the interview, observation, and documentation. The results showed (1) the strategic management of SD Islam De Green Camp begins with formulating a vision and mission that involves internal parties by involving all elements in the school; (2) De Green Camp Islamic Elementary School has good quality education services, and this is stated in the concept of child-friendly education; (3) De Green Camp Islamic Elementary School has a good quality educational environment and reflects an Islamic school; (4) De Green Camp Islamic Elementary School implements the 2013 curriculum by integrating Pendidikan Agama Islam/PAI (Islamic) subjects into each of its subjects; (5) De Green Camp Islamic Elementary School enroots principles in teachers to become individuals who have the potential to find solutions to every problem.